Pravno varstvo v postopkih podeljevanja koncesij - Štemberger Brizani, Katja (Podjetje in delo, 2023)
The paper discusses the legal protection in the concession award procedures. The author notes that the legal protection depends on the type and value of the concession. It is provided in accordance with the Legal Protection in Public Procurement Procedures Act in the case of concessions governed by the Certain Concession Contracts Act and works concessions under the Public-Private Partnership Act, or in accordance with the General Administrative Procedure Act and Administrative Dispute Act in the case of service concessions (not covered by the Certain Concession Contracts Act), or other concessions where a sectoral regulation provides for an administrative decision. In some cases, the legal protection under the above-mentioned laws for the same concession is also combined, which means that certain decisions issued in the procedure for its award are challenged under the General Administrative Procedure Act and Administrative Dispute Act, and certain decisions are challenged under the Legal Protection in Public Procurement Procedures Act, depending on whether they transpose the provisions of Directive 2014/23/EU or national law. Such dual regulation leads to a lack of clarity of the legal rules and difficulties in applying the legal provisions in practice. The legal protection of all concessions should therefore be unified and ensured in accordance with the Legal Protection in Public Procurement Procedures Act, with some adjustments to the rules, in particular as regards administrative dispute against decisions of the National Review Commission.
Keywords: koncesije; Koncesije (upravno pravo); poslovanje; pravno varstvo; revizijski postopek; sodbe; upravni akt; upravni spor